Los contenidos difundidos en la página oficial de facebook y su impacto en la imagen institucional del Gobierno Autónomo Descentralizado de la Parroquia de San Lorenzo, cantón Guaranda, provincia de Bolívar año 2021. - Fares Aylla, Adriana Emperatriz (2022)
The objective of the research work is to determine the contents disseminated on the official Facebook page and its impact on the institutional image of the Autonomous Decentralized Rural Parish Government of San Lorenzo, for which an analysis of the contents disseminated by the institution was carried out, verifying In this way, the importance of research because more and more people are getting involved with the digital world and that is how the audience is informed of the activities and actions carried out by the GADPR of San Lorenzo. The research was based on the method: qualitative and quantitative where the quality of the disseminated content was determined and how it affects the institutional image of the institution, which led to identifying the facts and phenomena in the study starting from the general aspects to reach individuals, therefore the study population was the 584 followers of the official Facebook page of the GADPR of San Lorenzo and 1 interview addressed to the person in charge of managing the institution's Facebook page. The results collected showed that the contents disseminated are not updated effectively and do not use the appropriate parameters and characteristics so that the information arrives in a timely manner and contributes positively to the institutional image, the investigation obtained allows us to conclude that the page should be updated every week or at least every fifteen days with well-structured and precise content to strengthen interaction and credibility with the audience, therefore, it is necessary to take into account the communication strategies proposed in the research for a good dissemination of content and a good institutional image.